Documentary and Information Communication in Public Administration: Legal Aspects and Digital Transformation - Kachkovska, Lesia; Blahovirna, Nataliia; Vozniuk , Yevheniia; Kryvtsov , Artem; Rohovyi , Borys; Shuliak, Antonina (International Journal of Basic and Applied Sciences, 2025)
The purpose of the scientific research is to analyze the use and determine the importance of documentary and communication activities in ‎public administration. The theoretical aspect of communication, legal support for the information activities of government bodies, is ‎characterized by the Official Internet Representation of the President of Ukraine, Volodymyr Zelenskyy is singled out as a public ‎institution of information support. The main characteristics and key aspects that are integral components in the formation and implementation ‎of state information policy are determined. The characteristics of legal support demonstrated that the Law of Ukraine “On Information” ‎defines the basic principles and mechanisms of access to information in Ukraine. The Law of Ukraine “On Access to Public Information” ‎specifies the procedure for access to public information held by subjects of government authority. The Law of Ukraine “On Citizens’ ‎Appeals” emphasizes the importance of documentary communication for ensuring the citizens’ right to appeal and receive answers from ‎government bodies. During the analysis of the topic, it was found that the main features of the effective use of information for management ‎purposes are completeness, relevance, and reliability. Information is the basis for decision-making in the public administration system, which is ‎used for analysis, planning, reporting, and control to increase the efficiency and transparency of the activities of administrative structures. ‎The level of information transparency for society is characterized, where information should be available to citizens by the ‎implementation of the accountability principle. At the same time, attention is focused on the importance of compliance with information ‎security requirements, especially regarding personal data or confidential information. The main generalizations on this problem are ‎providing citizens with public information as a key to maintaining the proper level of sovereignty. The effectiveness of such a process is ‎significantly increased when scientifically sound political and legal directions and clear ways of their implementation are functioning.‎n.